2016
DOI: 10.1002/anie.201605508
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Ring‐Opening Polymerization of O‐Carboxyanhydrides Using a β‐Diiminate Zinc Catalyst

Abstract: Recently O-carboxyanhydrides (OCAs) have emerged as a class of viable monomers which can undergo ring-opening polymerization (ROP) to prepare poly(α-hydroxyalkanoic acid) with functional groups that are typically difficult to achieve by ROP of lactones. Organocatalysts for the ROP of OCAs, such as dimethylaminopyridine (DMAP), may induce undesired epimerization of the α-carbon atom in polyesters resulting in the loss of isotacticity. Herein, we report the use of (BDI-IE)Zn(OCH(CH )COOCH ) ((BDI)Zn-1, (BDI-IE)=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 32 publications
(48 reference statements)
3
92
0
Order By: Relevance
“…Ring‐opening polymerization (ROP) of cyclic ester monomers is a versatile synthetic method for generating the well‐defined aliphatic polyesters. Various enzymatic, metal‐based catalysts, and organocatalysts have been developed for the ROP reactions of cyclic esters. Organocatalytic ROPs of cyclic esters have proven to be especially useful for the production of functional biodegradable polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Ring‐opening polymerization (ROP) of cyclic ester monomers is a versatile synthetic method for generating the well‐defined aliphatic polyesters. Various enzymatic, metal‐based catalysts, and organocatalysts have been developed for the ROP reactions of cyclic esters. Organocatalytic ROPs of cyclic esters have proven to be especially useful for the production of functional biodegradable polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…The development of facile synthetic strategy to functional biodegradable polymers continues to drive innovation in modern polymer chemistry and materials science . To date, considerable polymerization chemistry focuses on side chain functional polymers such as amidogen, carboxyl and disulfide as pendants along the polymer backbone.…”
Section: Methodsmentioning
confidence: 99%
“…The resultant polymers can be oxidizeda nd/orr educed by treatment with hydrogen peroxide (H 2 O 2 )o rdithiothreitol( DTT), highlighting their potentialf or applicationsi nt he stimuli-responsive field and inflammation/cancert argeting.W ith these desirable results, it is revealed that this versatile technique can provideabroad-reaching method to the next generation of innovative materials, especially,w ell-definedb iodegradable chalcogen-based main chain functional biomaterials.The development of facile synthetic strategyt of unctional biodegradable polymers continues to drive innovation in modern polymer chemistry and materials science. [1] To date, considerable polymerization chemistry focuses on side chain functional polymers such as amidogen, [2] carboxyl [3] andd isulfide [4] as pendantsalong the polymer backbone. In directcontrast, main chain functional polymers are poorly researched due in part to the challenges in preparing such polymers, in spite of the ubiquitous advantages, such as amplifieds ensitivity by incorporating responsive groups into main chain, improved solubility and selective or fast degradability of polymers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its success in early ROP investigations, DMAP was observed to induce transesterifications on the PLA backbone [29] and epimerizations on the chiral carbons. [30] To subdue the (super) strong bases that would incur transesterifications and racemizations, binary catalysts of bases and acids were developed for organocatalysis in ROPs [28b,e,31] that showed optimal compromise between efficiency and mildness. Based on a model of cocatalysis by base and acid in a ratio of 2:1 clarified by us [32] (Scheme 1, a), we proposed a new model of base and acid cocatalysts in a ratio of 1:1 in structured base and acid pair (Scheme 1, b).…”
Section: Introductionmentioning
confidence: 99%